A confined small-particle-size metal catalyst and a method for preparing small-diameter carbon nanotubes using the same
Patent Information
- Application Number
- CN202611210630.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-11
- Publication Date
- 2026-10-20
AI Technical Summary
[0005]有鉴于现有技术中金属催化剂活性组分在焙烧、还原及碳源裂解反应过程中易发生迁移、团聚和烧结,进而导致催化金属颗粒粒径增大、碳纳米管管径分布变宽、粗管比例升高以及无定形碳副产物增多的问题,本发明提供一种限域型小粒径金属催化剂及其制备小直径碳纳米管的方法
1、与现有技术相比,本发明通过真空浸润方式促进镍铜前驱体和限域剂充分进入介孔二氧化硅载体孔道内部,提高金属活性组分的孔内负载均匀性,减少孔口及外表面富集,从而降低还原后外表面团聚颗粒比例。
Smart Images

Figure FT_1 
Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] This invention relates to the field of catalysts and carbon nanotubes, and particularly to a confined small-particle-size metal catalyst and a method for preparing small-diameter carbon nanotubes. Background Technology
[0002] Carbon nanotubes possess high specific surface area, excellent electrical conductivity, mechanical properties, and chemical stability, making them widely applicable in electronic devices, composite materials, energy storage materials, and catalyst supports. Among them, small-diameter carbon nanotubes have attracted considerable attention due to their higher curvature and more unique electronic structure.
[0003] Currently, chemical vapor deposition (CVD) is a commonly used method for preparing carbon nanotubes, and its key lies in the size and dispersion state of the metal particles in the catalyst. Generally, the smaller and more uniformly distributed the catalytic metal particles, the more favorable it is for generating small-diameter, narrow-distribution carbon nanotubes. However, active metal components such as nickel and copper are prone to migration, agglomeration, and sintering during impregnation, drying, calcination, reduction, and carbon-donating reactions, leading to an increase in metal particle size. This, in turn, results in coarser carbon nanotube diameters and wider distributions, accompanied by problems such as increased amorphous carbon, higher ash content, and decreased yield.
[0004] CN112371131A discloses a carbon nanotube growth catalyst and its preparation method, as well as a method for preparing carbon nanotubes. This scheme uses a Fe-Co-Ni-Mo-Al pentagonal carbon nanotube growth catalyst, and improves the carbon nanotube growth rate by combining multi-metal components with the ethylene cracking reaction, enabling high-rate carbon nanotube production. CN111495381A discloses a method for preparing a sheet-like catalyst, the sheet-like catalyst, and its application in the preparation of ultrafine carbon nanotubes. This scheme uses a sheet-like catalyst to obtain carbon nanotubes with a diameter of 2-10 nm and improves the carbon nanotube yield. CN104084214A discloses a catalyst for preparing carbon nanotubes and its preparation method, as well as carbon nanotubes and their preparation method. This scheme uses metal oxide catalysts such as magnesium, aluminum, manganese, and cobalt to improve the carbon deposition rate, facilitating large-scale continuous production of carbon nanotubes. The patent literature reports that primarily focus on improving carbon nanotube yield and production rate through multi-metal components, sheet-like catalyst morphology, or co-precipitation processes. However, they fail to simultaneously address issues such as uniform loading of metal precursors within mesoporous channels, maintaining the small particle size of metal particles after reduction, preventing sintering during the carbon-supplying reaction, and ensuring the narrow distribution and growth of small-diameter carbon nanotubes. In practical applications, problems easily arise due to the migration, aggregation, or carbon deposition of the active metal components, leading to decreased catalytic activity, increased carbon nanotube diameter, wider diameter distribution, increased defect carbon, higher ash content, and a heavier purification burden. Therefore, there is an urgent need to construct a confined small-particle-size metal catalyst and a method for preparing small-diameter carbon nanotubes that simultaneously possesses coordination confinement, mesoporous channel confinement, pore-mouth silica shrinkage confinement, and pulsed carbon supply regulation. Summary of the Invention
[0005] In view of the problems in existing technologies where the active components of metal catalysts are prone to migration, agglomeration, and sintering during calcination, reduction, and carbon source pyrolysis reactions, leading to increased catalytic metal particle size, wider carbon nanotube diameter distribution, higher proportion of coarse nanotubes, and increased amorphous carbon byproducts, this invention provides a confined small-particle-size metal catalyst and a method for preparing small-diameter carbon nanotubes. This method uses a composite confining agent to coordinate and anchor the nickel-copper metal precursor, and combines this with mesoporous support pore loading, vacuum wetting, a silica-oxygen shrinkage layer at the pore opening, and pulsed carbon supply to maintain the small particle size and high dispersion of the metal active components during reduction and carbon supply reactions, thereby obtaining small-diameter, narrowly distributed carbon nanotubes with low defect rates.
[0006] To achieve the above objectives, the present invention provides a confined small-particle-size metal catalyst and a method for preparing small-diameter carbon nanotubes, comprising the following steps: S1. A sol-gel reaction is carried out using template agent, silicon source, alcohol-water mixed solvent and alkaline catalyst as raw materials. The template agent is removed by solid-liquid separation, washing, drying and calcination to obtain a mesoporous silica support. The mesoporous silica support is then acid-treated to obtain a pretreated mesoporous silica support. S2. Dissolve the nickel source, copper source, and precipitation aid in a first mixed solvent to obtain a nickel-copper precursor solution; dissolve or disperse the confinement agent in a second mixed solvent to obtain a confinement agent solution; mix the confinement agent solution with the nickel-copper precursor solution to obtain a nickel-copper precursor solution containing the confinement agent; add the pretreated mesoporous silica support to the nickel-copper precursor solution containing the confinement agent, and perform stirring, vacuum wetting, heating reaction, and drying treatment to load the nickel-copper precursor and confinement agent into the pores of the mesoporous silica support, obtaining a nickel-copper precursor mesoporous silica composite powder; subsequently, perform a secondary silicon source deposition treatment on the surface of the loaded nickel-copper precursor mesoporous silica composite powder, and perform solid-liquid separation, washing, drying, and calcination to obtain a nickel-copper oxide confinement catalyst precursor; place the nickel-copper oxide confinement catalyst precursor in an inert atmosphere and perform reduction activation under a hydrogen-containing atmosphere to obtain a confinement-type small-particle-size nickel-copper metal catalyst; S3. Subsequently, under the protection of an inert atmosphere, the temperature is raised to the carbon source decomposition temperature, and carbon nanotubes are grown using a pulsed carbon supply method to obtain a crude product of small-diameter carbon nanotubes containing a support; then, the crude product of small-diameter carbon nanotubes containing a support is subjected to alkali washing, acid washing, washing and drying in sequence to obtain small-diameter carbon nanotubes.
[0007] Furthermore, the template agent is a cationic surfactant; the silicon source is an orthosilicate silicon source; the alkaline catalyst is ammonia; and the acid treatment is performed using an inorganic acid solution.
[0008] Furthermore, the nickel source is a soluble nickel salt; the copper source is a soluble copper salt; the precipitation aid is urea; the first mixed solvent includes water and an alcohol solvent; and the second mixed solvent includes an amide solvent and an alcohol solvent.
[0009] Furthermore, the vacuum impregnation includes a cyclic operation of evacuation and introduction of inert gas to restore atmospheric pressure, in order to promote the entry of the nickel-copper precursor and confinement agent into the pores of the mesoporous silica carrier.
[0010] Furthermore, the secondary deposition treatment of the silicon source includes dispersing the loaded nickel-copper precursor mesoporous silica composite powder in a mixture of alcohol, water and alkaline catalyst, and then adding the silicon source to react, so that a silicon-oxygen shrinkage structure is formed at the pore opening of the mesoporous silica support.
[0011] Furthermore, the confinement agent includes at least one of nitrogen-containing polydentate coordination compounds and polycarboxylated organophosphorus nitrile compounds.
[0012] Furthermore, the pulsed carbon supply method includes an alternating carbon supply phase and an interval phase; during the carbon supply phase, a mixture of carbon source vapor, hydrogen, and inert gas is introduced into the reaction system; during the interval phase, the introduction of carbon source vapor is stopped, and a mixture of hydrogen and inert gas is introduced.
[0013] Furthermore, the carbon source is an alcohol-based carbon source; preferably, the carbon source is ethanol vapor.
[0014] Furthermore, the alkaline washing uses an alkaline solution to remove the silica carrier, and the acid washing uses an acidic solution to remove residual metal components and inorganic impurities.
[0015] Furthermore, a confined small-particle-size metal catalyst and a method for preparing small-diameter carbon nanotubes thereof include the following steps: S1 Weigh 1.5-2.5 g of hexadecyltrimethylammonium bromide and add it to a mixture of 450-520 mL of water and 100-150 mL of anhydrous ethanol. Stir at 35-45 °C until completely dissolved. Then add 5-9 mL of ammonia solution with a mass fraction of 20-28% and continue stirring for 20-40 min to obtain a template agent solution. While stirring, add 8-12 mL of tetraethyl orthosilicate dropwise to the template agent solution. After the addition is complete, continue the reaction for 4-8 h. After the reaction is complete, filter the solution. Wash the resulting filter cake with water and anhydrous ethanol, and then dry it at 70-90 °C for 8-12 h to obtain a silica precursor containing the template agent. The silica precursor was placed in a muffle furnace and heated to 520-580℃ at a heating rate of 0.5-2℃ / min, held at that temperature for 4-6 hours, and cooled to obtain a mesoporous silica support. 1.5-2.5 g of the mesoporous silica support was weighed and added to 80-120 mL of 40-60% (v / v) ethanol aqueous solution and dispersed for 10-30 min. Then, 3-8 mL of 0.03-0.08 mol / L hydrochloric acid solution was added and stirred at 45-60℃ for 1-3 hours. After the treatment was completed, the mixture was filtered, and the filter cake was washed with water until neutral, then washed with anhydrous ethanol, and then dried at 70-90℃ for 6-10 hours to obtain the pretreated mesoporous silica support. S2. Weigh 0.45-0.7 g of nickel nitrate hexahydrate, 0.08-0.18 g of copper nitrate trihydrate, and 0.2-0.45 g of urea, and add them to a mixed solvent consisting of 3-6 mL of water and 3-6 mL of anhydrous ethanol. Stir until homogeneous to obtain a nickel-copper precursor solution; add 0.02-0.05 g of limiting agent to 3-7 mL of... In a mixed solvent consisting of N,N-dimethylformamide and 2-5 mL of anhydrous ethanol, the mixture is ultrasonically dispersed for 5-20 min, then stirred for 10-30 min to obtain a confinement agent solution. This confinement agent solution is then added dropwise to the nickel-copper precursor solution while stirring continuously. After the addition is complete, stirring continues for 10-40 min to obtain a nickel-copper precursor solution containing the confinement agent. 1.5-2.5 g of the pretreated mesoporous silica support obtained in step S1 is weighed and added to the nickel-copper precursor solution containing the confinement agent. The mixture is first stirred for 20-50 min; then, it is placed in a vacuum environment and evacuated for 5-20 min, followed by the introduction of an inert gas to restore atmospheric pressure. The vacuum and atmospheric pressure cycles are repeated 2-5 times to allow the nickel-copper precursor and confinement agent to enter the mesoporous channels. After vacuum impregnation, the system is heated to 80-100℃ and stirred for 3-5 hours. After the reaction, the resulting solid is dried at 70-90℃ for 5-8 hours, and then dried at 110-130℃ for 3-5 hours to obtain a nickel-copper precursor-supported mesoporous silica composite powder. The nickel-copper precursor-supported mesoporous silica composite powder is added to a mixture of 80-120 mL anhydrous ethanol, 15-30 mL water, and 1-3 mL ammonia solution with a mass fraction of 20-28%, and stirred for 20-50 minutes. Then, tetraethyl orthosilicate is added... 0.15-0.4 mL was added dropwise to the above mixture. After the addition was complete, the mixture was stirred at 20-30℃ for 1-3 h. After the reaction was complete, the mixture was filtered, the filter cake was washed with anhydrous ethanol, and dried at 70-90℃ for 6-10 h to obtain the nickel-copper precursor confined complex. The nickel-copper precursor confined complex was placed in a muffle furnace and heated to 240-280℃ at a heating rate of 0.5-2℃ / min, and held at that temperature for 0.5-2 h. Then, the temperature was further increased to 400-460℃ at a heating rate of 1-3℃ / min, and held at that temperature for 1-3 h. The mixture was then naturally cooled to room temperature to obtain the nickel-copper oxide confined catalyst precursor. The nickel-copper oxide obtained in step S2 was weighed. 0.2-0.5 g of confined catalyst precursor is evenly spread in a quartz boat with a thickness not exceeding 3 mm. The quartz boat is placed in the middle of the constant temperature zone of a tube furnace. First, inert gas is introduced at a rate of 200-400 mL / min for 20-40 min to purge the air inside the tube. Then, under the protection of inert gas, the temperature is increased to 450-520 °C at a heating rate of 3-8 °C / min. A mixture of hydrogen and inert gas is introduced for reduction and activation, with a hydrogen flow rate of 40-80 mL / min and an inert gas flow rate of 200-300 mL / min. The reduction and activation time is 40-90 min, resulting in a confined small-particle-size nickel-copper metal catalyst. S3. After reduction and activation, the tube furnace is heated to 680-740℃ under inert gas protection, and carbon nanotubes are grown using a pulsed carbon supply method. Each carbon supply cycle includes a supply phase and an interval phase: During the supply phase, a mixed gas of ethanol vapor, hydrogen, and inert gas is introduced for 40-90 seconds, where the ethanol vapor is carried into the tube furnace by an inert gas bubbler at 20-30℃, with a flow rate of 140-220 mL / min for the inert gas carrying the ethanol vapor and a flow rate of 30-60 mL / min for the hydrogen; During the interval phase, the ethanol vapor is stopped, and a mixed gas of hydrogen and inert gas is introduced for 80-160 seconds, with a flow rate of 30-60 mL / min for the hydrogen and a flow rate of 180-260 mL / min for the inert gas; This carbon supply cycle is repeated 8-18 times; The reaction... After completion, the ethanol vapor and hydrogen gas were turned off, and inert gas was continuously introduced at a rate of 200-400 mL / min. The mixture was then cooled to room temperature under inert gas protection to obtain a crude product of small-diameter carbon nanotubes with a support. The crude product of small-diameter carbon nanotubes with a support was added to a 1-3 mol / L sodium hydroxide solution with a solid-liquid ratio of 1 g:(60-150) mL. The mixture was stirred at 70-90℃ for 3-6 h. After filtration, the filter cake was washed with water until the pH of the filtrate was less than 8. Subsequently, the obtained filter cake was added to a 0.5-2 mol / L hydrochloric acid solution with a solid-liquid ratio of 1 g:(50-120) mL. The mixture was stirred at 50-70℃ for 1-3 h. After acid washing, the mixture was filtered, and the filter cake was washed with water until neutral. Then it was washed with anhydrous ethanol and finally vacuum dried at 70-90℃ for 6-10 h to obtain small-diameter carbon nanotubes.
[0016] Further, the limiting agent is at least one of 2,2':6',2''-terpyridine-4'-carboxylic acid and hexa(4-carboxyphenoxy)cyclotriphosphazene; preferably, the limiting agent is a mixture of 2,2':6',2''-terpyridine-4'-carboxylic acid and hexa(4-carboxyphenoxy)cyclotriphosphazene in a ratio of (5-12):(18-35).
[0017] The present invention also provides a confined small-particle-size metal catalyst prepared by the above S1-S2 steps.
[0018] The present invention also provides a small-diameter carbon nanotube, which is obtained by the growth of ethanol carbon source by catalytic cracking of the above-mentioned confined small-particle-size metal catalyst.
[0019] In the preferred embodiment employing a composite confinement agent, vacuum impregnation, pore-hole silica shrinkage treatment, and pulsed carbon supply synergistic effect, the average diameter of the small-diameter carbon nanotubes is 0.8-3 nm, more preferably 1-2 nm; the proportion of carbon nanotubes larger than 5 nm is not higher than 8%.
[0020] The polydentate coordination of 2,2':6',2''-terpyridine-4'-carboxylic acid with nickel-copper metal ions enhances the immobilization ability of the metal precursor within the mesoporous channels. The multi-carboxyl structure and larger molecular framework of hexa(4-carboxyphenoxy)cyclotriphosphazene provide spatial separation and multi-point anchoring. Simultaneously, vacuum wetting promotes the penetration of the metal precursor into the deeper pores, while the silica shrinkage layer at the pore opening inhibits the migration of metal species. Pulsed carbon supply reduces carbon deposition and particle sintering caused by continuous carbon source supply. These combined techniques maintain the small particle size, high dispersion, and high stability of the nickel-copper metal particles during the reduction and carbon supply reactions.
[0021] The beneficial effects of this invention are: 1. Compared with the prior art, the present invention promotes the full entry of nickel-copper precursor and confinement agent into the pores of mesoporous silica carrier by vacuum impregnation, improves the uniformity of the loading of metal active components in the pores, reduces enrichment at the pore openings and outer surfaces, thereby reducing the proportion of agglomerated particles on the outer surface after reduction.
[0022] 2. Compared with the prior art, the present invention forms a silicon-oxygen shrinkage structure at the pore opening of the mesoporous carrier loaded with nickel-copper precursor by tetraethyl orthosilicate, which physically constrains the metal species in the pores and further inhibits the migration and sintering of the metal precursor during the roasting, reduction and carbon supply reaction processes.
[0023] 3. Compared with the prior art, the present invention uses a pulsed carbon supply method to grow carbon nanotubes. By alternating between the carbon supply stage and the interval stage, the risk of continuous supersaturation deposition of carbon species on the surface of metal particles is reduced, which helps to reduce the generation of amorphous carbon, inhibit the growth of metal particles during the reaction process, and obtain small-diameter, narrowly distributed carbon nanotubes.
[0024] 4. The carbon nanotubes obtained by this invention have the characteristics of small diameter, low proportion of thick tubes, low degree of defects, low ash content and high yield, and are suitable for application scenarios with high requirements for the diameter and structural uniformity of carbon nanotubes. Attached Figure Description
[0025] Figure 1 This is a scanning electron microscope image of the purified small-diameter carbon nanotubes obtained in Example 1. Detailed Implementation
[0026] The endpoints and any values of the ranges disclosed in this invention are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this invention.
[0027] Other raw materials not mentioned are all common raw materials. The above content is only for the purpose of illustrating the present invention and should not be construed as a strict limitation of the present invention. Those skilled in the art can directly purchase the same / similar raw materials from the market or prepare them themselves.
[0028] The technical solutions of the present invention will be clearly and completely described below with reference to specific embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0029] Example 1 A confined small-particle-size metal catalyst and a method for preparing small-diameter carbon nanotubes thereof, comprising the following steps: S1. Weigh 2g of hexadecyltrimethylammonium bromide and add it to a mixture of 480mL water and 120mL anhydrous ethanol. Stir at 400r / min at 40℃ until completely dissolved. Then add 7mL of 25% ammonia solution and continue stirring at 400r / min for 30min to obtain the template agent solution. While stirring, add 10mL of tetraethyl orthosilicate dropwise to the template agent solution at a rate of 0.5mL / min, maintaining a stirring speed of 500r / min during the dropwise addition. After the dropwise addition is completed, continue the reaction at 40℃ and 500r / min for 6h. After the reaction is completed, filter the solution. Wash the filter cake successively with water and anhydrous ethanol and place it in a container. The silica precursor containing the template agent was dried in an 80℃ forced-air drying oven for 10 hours to obtain a silica precursor containing the template agent. The silica precursor containing the template agent was placed in a muffle furnace and heated to 550℃ at a rate of 1℃ / min and held for 5 hours. After cooling, a mesoporous silica support was obtained. 2g of the mesoporous silica support obtained above was added to 100mL of 50% ethanol aqueous solution and ultrasonically dispersed for 20min. Then 5mL of 0.05mol / L hydrochloric acid solution was added and stirred at 50℃ for 2 hours. After the treatment was completed, the mixture was filtered, and the filter cake was washed with water until the pH of the filtrate was 7. It was then washed twice with anhydrous ethanol and placed in an 80℃ vacuum drying oven for 8 hours to obtain the pretreated mesoporous silica support. S2 Weigh 0.58 g of nickel nitrate hexahydrate, 0.12 g of copper nitrate trihydrate, and 0.3 g of urea and add them to a mixed solvent consisting of 4 mL of water and 4 mL of anhydrous ethanol. Stir at 300 r / min until homogeneous to obtain a nickel-copper precursor solution; add 0.033 g of limiting agent to 5 mL The mixture of N,N-dimethylformamide and 3 mL of anhydrous ethanol was ultrasonically dispersed for 10 min, then stirred at 300 r / min for 20 min to obtain a confinement agent solution. This confinement agent solution was added dropwise to the nickel-copper precursor solution at a rate of 0.2 mL / min, maintaining a stirring speed of 300 r / min during the addition. After the addition was complete, stirring was continued at 300 r / min for 20 min to obtain a nickel-copper precursor solution containing the confinement agent. The pretreated mesoporous silica support obtained in step S1 was added to the nickel-copper precursor solution containing the confinement agent, and stirred at 400 r / min for 30 min. Then, the solution was placed in a vacuum desiccator and evacuated for 10 min, followed by nitrogen gas to restore atmospheric pressure. This process was repeated three times. After vacuum impregnation, the system was heated to 90 °C and stirred at 300 r / min for 4 h. After the reaction was complete, the resulting solid was dried at 80 °C for 6 h, and then dried at 120 °C for 4 h to obtain the supported nickel-copper precursor. Mesoporous silica composite powder as a precursor; the nickel-copper precursor mesoporous silica composite powder was dispersed in a mixture of 100 mL anhydrous ethanol, 20 mL water, and 2 mL 25% ammonia solution and stirred at 400 rpm for 30 min; then 0.25 mL of tetraethyl orthosilicate was added dropwise to the mixture at a rate of 0.025 mL / min, maintaining a stirring speed of 400 rpm during the addition. After the addition was completed, the mixture was stirred at 25 °C at a rate of 400 rpm. The mixture was stirred at 00 r / min for 2 h. After the reaction was completed, it was filtered, and the filter cake was washed three times with anhydrous ethanol and dried at 80 °C for 8 h to obtain the nickel-copper precursor confined complex. The above nickel-copper precursor confined complex was placed in a muffle furnace and heated to 260 °C at a rate of 1 °C / min and held for 1 h. Then, the temperature was further increased to 430 °C at a rate of 2 °C / min and held for 2 h. After natural cooling to room temperature, the nickel-copper oxide confined catalyst precursor was obtained. 0.3g of the catalyst was evenly spread in a quartz boat, with a thickness not exceeding 2mm. The quartz boat was placed in the middle of the constant temperature zone of a tube furnace. Argon gas was first introduced at a rate of 300mL / min for 30min to purge the air from the tube. Then, under argon protection, the temperature was increased to 480℃ at a rate of 5℃ / min. A mixture of hydrogen and argon gas was introduced for reduction activation, with a hydrogen flow rate of 60mL / min and an argon flow rate of 240mL / min. The reduction time was 60min, resulting in a confined small-particle-size nickel-copper metal catalyst. The confining agent was a mixture of 2,2':6',2''-terpyridine-4'-carboxylic acid (CAS: 148332-36-9) and hexa(4-carboxyphenoxy)cyclotriphosphazene in a mass ratio of 8:25. After S3 reduction and activation, the tube furnace was heated to 710℃ under argon protection. After heating, carbon nanotubes were grown using a pulsed carbon supply method. Each carbon supply cycle included a supply phase and an interval phase: During the supply phase, a mixture of ethanol vapor, hydrogen, and argon was introduced for 60 seconds, with the ethanol vapor carried into the tube furnace by argon through a 25℃ ethanol bubbling bottle at a flow rate of 180 mL / min and the hydrogen flow rate of 40 mL / min. During the interval phase, the ethanol vapor supply was stopped, and a mixture of hydrogen and argon was introduced for 120 seconds, with a hydrogen flow rate of 40 mL / min and an argon flow rate of 220 mL / min. This carbon supply cycle was repeated 12 times. After the reaction was completed, the ethanol vapor and hydrogen supply were turned off. Argon gas was continuously introduced at a rate of 300 mL / min, and the temperature was lowered to room temperature under argon protection to obtain a crude product of small-diameter carbon nanotubes containing a support. The crude product of small-diameter carbon nanotubes containing a support was added to a 2 mol / L sodium hydroxide solution with a solid-liquid ratio of 1 g: 100 mL. The mixture was stirred at 300 r / min for 4 h at 80 °C. After filtration, the filter cake was washed with water until the pH of the filtrate was less than 8. The filter cake was then added to a 1 mol / L hydrochloric acid solution with a solid-liquid ratio of 1 g: 80 mL. The mixture was stirred at 300 r / min for 2 h at 60 °C. After acid washing, the mixture was filtered, and the filter cake was washed with water until neutral. It was then washed once with anhydrous ethanol and finally dried in a vacuum drying oven at 80 °C for 8 h to obtain small-diameter carbon nanotubes.
[0030] Example 2 The procedure is basically the same as in Example 1, except that the limiting agent is 2,2':6',2''-terpyridine-4'-carboxylic acid, and the rest of the steps are the same as in Example 1.
[0031] Example 3 The process is basically the same as in Example 1, except that the limiting agent is hexa(4-carboxyphenoxy)cyclotriphosphazene, and the other steps are the same as in Example 1.
[0032] Example 4 The process is basically the same as in Example 1, except that 2,2':6',2''-terpyridine-4'-carboxylic acid and hexa(4-carboxyphenoxy)cyclotriphosphazene are not added in step S2, the preparation and dropwise addition of the confinement agent solution are omitted, and an equal volume of the second mixed solvent is used instead of the confinement agent solution. The remaining steps are the same as in Example 1.
[0033] Example 5 The process is basically the same as in Example 4, except that in step S2, tetraethyl orthosilicate is not added to form a silica shrinkage layer at the pore opening. That is, the loaded nickel-copper precursor mesoporous silica composite powder is no longer dispersed in a mixture of anhydrous ethanol, water and ammonia, and 0.25 mL of tetraethyl orthosilicate is no longer added for pore shrinkage treatment. Instead, the loaded nickel-copper precursor mesoporous silica composite powder is directly dried at 80°C for 8 hours and then subjected to subsequent calcination, reduction activation and carbon nanotube growth. The other steps, unless otherwise specified, are the same as in Example 4. For the parts of Example 4 not specified, refer to Example 1.
[0034] Example 6 The process is basically the same as in Example 1, except that: in step S2, the vacuum impregnation treatment of evacuation and nitrogen gas to restore normal pressure is not performed. Instead, after adding the pretreated mesoporous silica support obtained in step S1 to the nickel-copper precursor solution containing the confinement agent, the mixture is stirred at 400 r / min for 30 min, and then directly heated to 90°C and stirred at 300 r / min for 4 h. The remaining steps are the same as in Example 1.
[0035] Example 7 The process is essentially the same as in Example 1, except that in step S3, instead of pulsed carbon supply, a mixture of ethanol vapor, hydrogen, and argon is continuously introduced at 710°C for 12 minutes to maintain the cumulative ethanol supply time consistent with the total carbon supply stage in Example 1. The ethanol vapor is carried into the tube furnace by argon gas through a 25°C ethanol bubbling flask, with an argon flow rate of 180 mL / min and a hydrogen flow rate of 40 mL / min. After the reaction is complete, the ethanol vapor and hydrogen are shut off, and argon gas is continued to be introduced at 300 mL / min. The furnace is then cooled to room temperature under argon protection. The remaining steps are the same as in Example 1.
[0036] Example 8 The process is basically the same as in Example 1, except that in step S2, 0.033g of the limiting agent is replaced with 0.033g of citric acid, and the rest of the steps are the same as in Example 1.
[0037] Test Example 1 (1) Mesoporous structure testing; The nickel-copper oxide confined catalyst precursor, after calcination and before reduction, was used as the test sample in the examples. Before testing, the sample was degassed under vacuum at 120°C for 6 hours, and then the specific surface area, pore volume, and pore size distribution of the sample were measured using a nitrogen adsorption-desorption apparatus. The specific surface area was calculated using the BET method, and the pore size distribution was calculated using the BJH method.
[0038] (2) Particle size test of the reduced metal particles; Take 0.3 g of the nickel-copper oxide confined catalyst precursor obtained in each example and reduce it according to the reduction and activation conditions corresponding to each example. After reduction, cool to room temperature under argon protection, and then passivate for 30 min by introducing a 1% (v / v) oxygen / argon mixture. Take a small amount of the passivated sample, add it to anhydrous ethanol, ultrasonically disperse for 5 min, drop it onto the surface of a copper mesh, and observe the dispersion state of the metal particles using a transmission electron microscope after natural drying. Randomly select no less than 10 fields of view for each sample, count no less than 200 identifiable metal particles, and calculate the average particle size.
[0039] Among them, metal particles with a diameter greater than 5 nm and located on the outer surface of the carrier or outside the pore are denoted as external agglomerates, and their proportion in the total number of identifiable metal particles is counted.
[0040] Table 1. Mesoporous structure of catalyst precursor and test results of dispersion performance of reduced metal particles
[0041] As shown in Table 1, Example 1 uses 2,2':6',2''-terpyridine-4'-carboxylic acid and hexa(4-carboxyphenoxy)cyclotriphosphazene as composite confinement agents, combined with vacuum wetting and orifice silica shrinkage treatment. Therefore, the average particle size of the reduced metal particles is only 1.28 nm, and the proportion of agglomerated particles on the outer surface is 3.6%, exhibiting the best metal dispersion effect. This is because the terpyridine structure can form coordination and fixation with nickel and copper ions, while the polycarboxyl structure of the cyclotriphosphazene can provide multi-point anchoring and steric hindrance. The two work synergistically to confine the metal particles. The migration, enrichment, and agglomeration of metal precursors during calcination and reduction processes were studied. Example 2 used only 2,2':6',2''-terpyridine-4'-carboxylic acid, and Example 3 used only hexa(4-carboxyphenoxy)cyclotriphosphazene. After reduction, the average particle size of the metal particles increased to 1.86 nm and 1.78 nm, respectively, and the proportion of agglomerated particles on the outer surface increased to 8.9% and 8.1%, respectively. This indicates that although a single confinement agent has a certain coordination or spatial confinement effect, it is difficult to simultaneously achieve both metal ion fixation and interparticle isolation, so the effect is weaker than that of Example 1.
[0042] In Example 4, without the aforementioned composite confinement agent, although the BET specific surface area and average pore size increased, the average particle size of the reduced metal particles increased to 2.46 nm, and the proportion of agglomerated particles on the outer surface increased to 17.8%. This indicates that relying solely on the mesoporous support itself is insufficient to effectively fix the nickel-copper precursor. Metal species easily migrate to the pore openings or the outer surface of the support and agglomerate during heat treatment. In Example 5, the pore opening silica shrinkage layer was further removed, resulting in an increase in the average particle size of the metal particles to 2.88 nm, and the proportion of agglomerated particles on the outer surface reached 23.6%. This demonstrates that the pore opening shrinkage structure plays a crucial role in restricting the migration of metal species; the absence of this structure further exacerbates metal particle growth and... External agglomeration; Example 6 did not undergo vacuum wetting treatment, and its reduced metal particles had an average particle size of 1.93 nm and an external agglomeration particle ratio of 10.4%, indicating that vacuum wetting can promote the full entry of nickel-copper precursor and confinement agent into the mesoporous channels and improve the uniformity of loading inside the pores; without this step, some metal precursors are prone to remain at the pore opening or outer surface, resulting in larger particles after reduction; Example 7 only changed the subsequent carbon supply method, and the catalyst preparation stage was basically the same; Example 8 used citric acid to replace the composite confinement agent, which could produce a certain complexation effect, but its spatial confinement and thermal stability were insufficient, so the average particle size and agglomeration ratio of metal particles were still significantly higher than those of Example 1.
[0043] Test Example 2 (1) Stability test of metal particles after reaction; The crude product of the supported carbon nanotubes after the S3 carbon-donating reaction in Example 1, after cooling, was used to observe the dispersion state of the metal particles after the reaction using transmission electron microscopy, without any alkali or acid washing treatment. At least 200 metal particles were counted for each sample, and the average particle size after the reaction was calculated. This test was used to evaluate whether the metal particles grew, overflowed, or sintered during the carbon-donating reaction.
[0044] (2) Carbon nanotube diameter test: The purified small-diameter carbon nanotubes obtained in the examples were added to anhydrous ethanol and ultrasonically dispersed for 30 min. The mixture was then dropped onto a copper mesh surface and allowed to dry naturally. The morphology of the carbon nanotubes was observed using a transmission electron microscope. The outer diameter of at least 200 carbon nanotubes from each sample was randomly counted, and the average diameter and main diameter distribution range were calculated. Carbon nanotubes with an outer diameter greater than 5 nm were designated as large-diameter carbon nanotubes, and their proportion was recorded.
[0045] Table 2. Results of test on the stability of metal particles and the diameter distribution of carbon nanotubes after reaction.
[0046] As shown in Table 2, after the reaction in Example 1, the average particle size of the metal particles was 1.46 nm, and the average diameter of the carbon nanotubes was 1.42 nm. The proportion of carbon nanotubes larger than 5 nm was only 1.4%, indicating that the metal particles maintained good small-size stability during the high-temperature carbon supply process. Since the diameter of carbon nanotubes is usually controlled by the size of the catalytic metal particles, the stable small-diameter nickel-copper particles in Example 1 are conducive to the formation of small-diameter, narrow-distribution carbon nanotubes. In Examples 2-3, since only a single confinement agent was used, the average particle size of the metal particles increased to 2.18 nm and 2.03 nm, respectively, and the average diameter of the carbon nanotubes increased to 2.11 nm and 1.98 nm, respectively. The proportion of carbon nanotubes larger than 5 nm also increased to 5.9% and 5.1%, respectively. This indicates that the single confinement agent is insufficient in resisting sintering and migration of the metal particles during the high-temperature reaction, leading to particle growth and further inducing the formation of coarser carbon nanotubes. In Example 4, no composite confinement agent was added. In Example 5, the pore-hole silica shrinkage layer was further removed. After the reaction, the average particle size of the metal particles increased to 2.91 nm and 3.35 nm, respectively, and the average diameter of the carbon nanotubes increased to 2.81 nm and 3.12 nm, respectively. The proportion of carbon nanotubes larger than 5 nm reached 13.2% and 17.5%, respectively. This indicates that without the confinement agent and the pore-hole shrinkage structure, the metal particles are more likely to migrate, sinter, and overflow during the carbon supply process, thereby forming large particle catalytic centers, resulting in an increase in the diameter and wider distribution of carbon nanotubes.
[0047] In Example 6, due to the lack of vacuum impregnation, the initial pore distribution of the metal precursor was uneven, and the average particle size of the metal particles and the average diameter of the carbon nanotubes increased to 2.37 nm and 2.35 nm, respectively, after the reaction. In Example 7, although the particle state after reduction was similar to that of Example 1, the average particle size of the metal particles increased to 2.08 nm after the reaction and the proportion of carbon nanotubes larger than 5 nm increased to 6.7% after the continuous carbon supply method, indicating that continuous carbon supply easily causes excessive deposition of carbon species on the surface of metal particles, inducing particle sintering or instability. In Example 8, citric acid was used as a confinement agent, but due to its insufficient confinement ability, the diameter of the particles and carbon nanotubes after the reaction was significantly larger than that of Example 1.
[0048] Test Example 3 (1) The structure of the purified carbon nanotubes obtained in the example was tested using Raman spectroscopy. The excitation wavelength was 532 nm, and the scanning range was 100-3200 cm⁻¹. -1 Record the intensities of the D and G peaks and calculate the ID / IG value. The lower the ID / IG value, the lower the degree of defects and the lower the proportion of amorphous carbon in the carbon nanotubes.
[0049] (2) The purified small-diameter carbon nanotubes obtained in the example were subjected to thermogravimetric analysis in air atmosphere. The heating rate was 10℃ / min, and the test temperature range was room temperature to 800℃. The percentage of the residual mass at 800℃ to the initial sample mass was used as the ash content to evaluate the removal of residual metals and inorganic carriers.
[0050] (3) Weigh the catalyst after reduction and activation, m0; weigh the crude product containing supported carbon nanotubes obtained after S3 carbon supply reaction and cooling, m1; and calculate the weight gain rate of the crude product according to the following formula: Crude product weight gain rate = (m1-m0) / m0×100%.
[0051] Weigh the purified carbon nanotubes obtained after alkali washing, acid washing, and drying, and calculate the purified carbon nanotube yield using the following formula: Purified carbon nanotube yield = m2 / m0.
[0052] Table 3. Test results of structural defects, ash content and yield of carbon nanotubes.
[0053] As shown in Table 3, Example 1 had a Raman ID / IG value of 0.16, an ash content of 2.3 wt%, a crude product weight gain of 186%, and a purified carbon nanotube yield of 1.21 g / g catalyst, indicating the best overall results. These results are consistent with the trend in Tables 1-2 where Example 1 exhibited smaller metal particle size, less agglomeration, and better post-reaction stability. Small and uniform metal particles can provide stable nucleation sites, reduce the formation of amorphous and defective carbon, and simultaneously improve catalyst utilization and product purification efficiency.
[0054] In Examples 2-3, due to insufficient action of a single confinement agent, the ID / IG values increased to 0.25 and 0.23, respectively, and the ash content increased to 4.8 wt% and 4.4 wt%, respectively. The yields were lower than in Example 1, indicating that moderate growth of metal particles leads to an increase in defects in carbon nanotubes and makes it more difficult to completely remove residual metal or inorganic components. In Examples 4-5, due to the lack of a composite confinement agent, and in Example 5, the lack of a pore-hole silica shrinkage layer, the growth and agglomeration of metal particles were more obvious. Therefore, the ID / IG values increased to 0.34 and 0.39, respectively, and the ash content increased to 6.9 wt% and 8.1 wt%, respectively. The purification yields decreased to 0.88 g / g catalyst and 0.79 g / g catalyst, respectively. These results indicate that uncontrolled growth of metal particles increases coarse tubes, defective carbon, and inorganic residues, while reducing effective catalytic activity.
[0055] Example 6 did not undergo vacuum impregnation, resulting in decreased uniformity of loading within the pores. Consequently, the ID / IG value, ash content, and yield were all inferior to those of Example 1. Example 7 used continuous carbon supply. Although the initial catalyst structure was similar to that of Example 1, continuous carbon source supply easily caused carbon deposition, particle coating, and local sintering, leading to an increase in ID / IG value, ash content, and yield. Example 8 used citric acid instead of the composite confinement agent. Since it could not maintain a stable confinement structure during high-temperature reactions, the final product defects, ash content, and yield were all inferior to those of Example 1.
[0056] The preferred embodiments of the present invention have been described in detail above. It should be understood that those skilled in the art can make numerous modifications and variations based on the concept of the present invention without creative effort. Therefore, all technical solutions that can be obtained by those skilled in the art based on the concept of the present invention through logical analysis, reasoning, or limited experimentation on the basis of existing technology should be within the scope of protection defined by the claims.
Claims
1. A method for preparing a confined small-particle-size metal catalyst, characterized in that: Includes the following steps: S1. A sol-gel reaction is carried out using template agent, silicon source, alcohol-water mixed solvent and alkaline catalyst as raw materials. The template agent is removed by solid-liquid separation, washing, drying and calcination to obtain a mesoporous silica support. The mesoporous silica support is then acid-treated to obtain a pretreated mesoporous silica support. S2. Dissolve the nickel source, copper source, and precipitation aid in a first mixed solvent to obtain a nickel-copper precursor solution; dissolve or disperse the confinement agent in a second mixed solvent to obtain a confinement agent solution; mix the confinement agent solution with the nickel-copper precursor solution to obtain a nickel-copper precursor solution containing the confinement agent. The pretreated mesoporous silica support was added to the nickel-copper precursor solution containing the confinement agent. After stirring, vacuum impregnation, heating reaction, and drying, a supported nickel-copper precursor mesoporous silica composite powder was obtained. Subsequently, a secondary silicon source deposition treatment was performed on the surface of the supported nickel-copper precursor mesoporous silica composite powder. After solid-liquid separation, washing, drying, and calcination, a nickel-copper oxide confinement catalyst precursor was obtained. The nickel-copper oxide confinement catalyst precursor was placed in an inert atmosphere and reduced and activated under a hydrogen-containing atmosphere to obtain a confinement-type small-particle-size nickel-copper metal catalyst. The confinement agent includes at least one of nitrogen-containing polydentate coordination compounds and polycarboxylated organophosphorus nitrile compounds.
2. The method for preparing the confined small-particle-size metal catalyst as described in claim 1, characterized in that: The template agent is a cationic surfactant; the silicon source is an orthosilicate silicon source; the alkaline catalyst is ammonia; and the acid treatment is performed using an inorganic acid solution.
3. The method for preparing the confined small-particle-size metal catalyst as described in claim 1, characterized in that: In step S2, the nickel source is a soluble nickel salt, the copper source is a soluble copper salt, and the precipitation aid is urea.
4. The method for preparing the confined small-particle-size metal catalyst as described in claim 1, characterized in that: The confinement agent is at least one of 2,2':6',2''-terpyridine-4'-carboxylic acid and hexa(4-carboxyphenoxy)cyclotriphosphazene.
5. A confined small-particle-size metal catalyst, characterized in that: It is prepared by the preparation method according to any one of claims 1-4.
6. A method for preparing small-diameter carbon nanotubes, characterized in that, Using the confined small-particle-size metal catalyst as described in claim 5, the temperature is raised to the carbon source decomposition temperature under an inert atmosphere, and carbon source vapor is decomposed and grown into carbon nanotubes under the action of the confined small-particle-size metal catalyst using a pulse carbon supply method. Small-diameter carbon nanotubes are then prepared by purification treatment.
7. The method for preparing small-diameter carbon nanotubes as described in claim 6, characterized in that, The pulsed carbon supply method includes alternating carbon supply phases and interval phases; during the carbon supply phase, a mixture of carbon source vapor, hydrogen, and inert gas is introduced; during the interval phase, the introduction of carbon source vapor is stopped, and a mixture of hydrogen and inert gas is introduced.
8. The method for preparing small-diameter carbon nanotubes as described in claim 7, characterized in that: The carbon supply phase lasts for 40-90 seconds, the interval phase lasts for 80-160 seconds, and the carbon supply phase and the interval phase are repeated 8-18 times.
9. The method for preparing small-diameter carbon nanotubes as described in claim 7, characterized in that: During the carbon supply stage, ethanol vapor is carried into the reaction zone by an inert gas through an ethanol bubbling bottle at 20-30°C. The flow rate of the inert gas carrying the ethanol vapor is 140-220 mL / min, and the flow rate of hydrogen is 30-60 mL / min. During the interval stage, the flow rate of hydrogen is 30-60 mL / min, and the flow rate of inert gas is 180-260 mL / min.
10. The method for preparing small-diameter carbon nanotubes as described in claim 6, characterized in that: The purification process includes sequential alkaline washing, acid washing, rinsing, and drying; the alkaline washing uses a 1-3 mol / L sodium hydroxide solution with a solid-liquid ratio of 1 g:(60-150) mL, and is stirred at 70-90℃ for 3-6 h; the acid washing uses a 0.5-2 mol / L hydrochloric acid solution with a solid-liquid ratio of 1 g:(50-120) mL, and is stirred at 50-70℃ for 1-3 h.
Citation Information
Patent Citations
Catalyst for preparing carbon nanotube, preparation method of catalyst, carbon nanotube, preparation method of carbon nanotube and lithium ion battery
CN104084214A
Preparation method of flaky catalyst, flaky catalyst and application of flaky catalyst in preparation of ultrafine carbon nanotubes
CN111495381A
Carbon nanotube growth catalyst and preparation method thereof, and preparation method of carbon nanotube
CN112371131A